Characterization of Antibiotics and Antibiotic Resistance Genes on an Ecological Farm System - Songhe Zhang; Ju Gu; Chao Wang; Peifang Wang; Shaojun Jiao; ZhenLi He; Bing Han (Journal of Chemistry)
There is a growing concern worldwide about the prevalence of antibiotics and antibiotic resistance genes (ARGs) on the farm. In this study, we investigated the distribution of seven antibiotics and ten ARGs in fresh and dried pig feces, in biogas slurry, and in grape-planting soil from an ecological farm. Antibiotics including sulfamethazine, norfloxacin, ofloxacin, tetracycline, oxytetracycline, and chlortetracycline were detected in these samples (except for sulfamethoxazole) in dried feces. In general, antibiotics levels in samples were in the sequence: biogas slurry > fresh feces > soil or dried feces. Results of ecological risk assessments revealed that among the seven antibiotics chlortetracycline showed the highest ecological risk. Among the ten ARGs, sulI and tetO were the most prevalent on this ecological farm. There were positive correlations between certain ARGs and the corresponding antibiotics on this ecological farm. Therefore, continuous monitoring of antibiotics and their corresponding ARGs should be conducted in the agroecosystem near the concentrated animal farming operation systems.